Some operations on lattice implication algebras - E. H. Roh; S. Y. Kim; Y. Xu; Young Bae Jun (International Journal of Mathematics and Mathematical Sciences)
We introduce the concept of a ⊗-closed set and a ⊗-homomorphism in lattice implication algebras, and we discuss some of their properties. Next, we introduce the fuzzy implicative filter and obtain equivalent conditions. Finally, we discuss the operation ⊗, fuzzy filters and fuzzy implicative filters.